ANALISIS PENERAPAN TBTQ DALAM MENINGKATKAN KEMAMPUAN MEBACA TULIS AL-QUR’AN DI MIM KALIMANAH WETAN - Nurul Afifah; Nashokah Nashokah; Chairani Astina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the importance of students' ability to read and write the Qur'an and the Tuntas Baca Tulis Al-Qur'an (TBTQ) program implemented at MIM Kalimanah Wetan. This study aims to describe the implementation of the TBTQ program, analyze students' ability to read and write the Qur'an, and identify supporting and inhibiting factors in TBTQ implementation. In this thesis, the researcher employed a qualitative approach with a field research design. Data were collected through observation, interviews, and documentation. Data analysis was conducted using data reduction, data display, and conclusion drawing or verification to facilitate the understanding of the phenomena and problems encountered and to provide solutions to existing issues. The results of the study indicate that: 1) The learning process of Qur'anic reading and writing was carried out through the stages of planning, implementation, and evaluation. The program was conducted four times a week from 06.30 am. to 07.30 a.m. before regular lessons using the Iqra' method and a private tutoring system adjusted to students abilities. Evaluation was conducted through monitoring students' progress in reading and writing the Qur'an, reading tests, writing tests, and recording learning outcomes on achievement cards. 2) Students Qur'anic reading and writing abilities showed varying levels of achievement according to their grade levels and individual abilities. This was reflected in their improved reading fluency, correct pronunciation of letters based on makharij al-huruf, application of basic tajwid rules, and ability to write hijaiyah letters and Qur'anic verses according to their level of competence. 3) Supporting factors of the TBTQ program included school support, teacher competence, facilities and infrastructure, and students enthusiasm, while inhibiting factors included differences in students abilities, limited time, and students' lack of focus during the learning proces.